The background culture of modernity as the factor of moral transformations of the age - Rogozha (Ukrainian Cultural Studies, 2022)
Axiological transformations of the epoch of Modernity are in the sight of researchers from different fields of social sciences and humanities. They are key for understanding of different processes in the contemporary world. Simultaneously, shaping circumstances of the epoch which made those spiritual transformations possible usually remain beyond scholars’ concern. The main attention of the current article is focused on research of Modernity immediate social practice, which generated specific spiritual mood of the age, accumulated in the Enlightenment programs and simultaneously was influenced and corrected by those programs. John Rawls’s concept of the background culture became the theoretical ground for the article. The background culture of the epoch of Modernity is comprehended as immediate immanent social experience of the civil society caused by social institutions created in that period. The involving of the individual in that experience allowed him / her to comprehend basic socio-moral values as directed on optimization of public interaction. Components of the background culture are: great geographical discoveries, the development of the industrial economy, Reformation and religious wars, early bourgeois revolutions, forming of national constitutional governments. Basic socio-moral values of the background culture are: frontier as Zeitgeist when expansivity and the habit to live in conditions of the stable instability in permanent changeable world were incorporated; individualism as the result of synthesis of free economic activity and the protestant enthusiasm with its internal religiosity of the believer; compelled (mechanic) solidarity, conditioned by the rational economy; tolerance as the derivative from the modus vivendi principle in conditions of competing the good life strategies based on religious believes; law-abiding as the unity of traditional medieval and Anglo-Saxon law with the comprehension of necessity to follow legal norms for civil peace and economic prosperity.